EFEKTIFITAS VIRTUAL CLASS BERBASIS SCAFFOLDING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS MAHASISWA - Noer Hodijah, Siti Romlah; Sudiana, Ria; Murni, Dewi (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
The low logical thinking ability of students causes them to experience difficulties in making the reasoning of genetic concepts. This study aims to examine the effectiveness of scaffolding based virtual class to improve student’s logical thinking ability. Quasi experiment was used in this study. The population was the 4th semester students of Biology education of Faculty of Teacher Training and Education at one of University at Serang, Indonesia, Academic Year 2016/2017, taking the Genetics course. Samples were taken randomly. The student’s logical thinking ability was measured by using the Test of Logical Thinking Ability (TOLT). The students pretest results of logical thinking ability in the experimental and control classes show the same average value of 2.64 included in the transition category, whereas post test results show different values. The experimental class indicates an average grade of 6.41 and a control class of 4.13, although the average difference between the two groups is significantly different, but both still show the same category of initial formal. Based on Mann-Whitney statistical test results, there is a difference of logical thinking ability between the two treatment classes. This can be interpreted that learning by using scaffolding based virtual class is effective in improving student’s logical thinking ability.